PRODUK MIE SEHAT DAUN KELOR PADA SISWA(i) SMAN 13 MAROS - Aminah, Aminah; Hamsinah, Hamsinah; Ririn (Jurusan Farmasi FMIPA Universitas Tadulako, 2023)
ABSTRACT Teenagers are age groups that are vulnerable to experiencing malnutrition problems, the presence of adolescent eating patterns that can affect adolescent nutritional status, including not always having breakfast, most teenagers eat less vegetable fibers and fruit, and often consume foods. In addition, adolescents also tend to lack physical activity. Noodles are a favorite food for children and teenagers and even adults. With the problem of the servant, it is planning to hold a devotion in one of the UMI fostered villages namely Pucak Village, Maros, more precisely at the School of SMAN 13 Maros. This school is a school with quite a large number of students but the average tease posture is small, so that the servant designs a popular food formula that has a high nutritional content, especially calcium. The implementation method will later provide the questionnaire at the beginning to measure students 'abilities, conduct counseling to increase students' understanding, followed by demonstrating how to make noodles from Moringa leaves and then train students to make noodles independently, then ended with questionnaires as a form of participant evaluation. The results of this service are very interesting and enthusiastic, especially among our teachers and products, it is very popular with school children. Conclusion this activity where students experience an increase in understanding and product of healthy Moringa Noodle, our Moringa is liked by children and teachers at SMAN 13 Maros. Keywords: Nutrition, Noodles, Moringa, SMAN 13Maros ABSTRAK Remaja merupakan kelompok usia yang rentan mengalami masalah gizi kurang ataupun lebih, adanya pola makan remaja yang tidak baik yang dapat memengaruhi status gizi remaja diantaranya tidak selalu sarapan, sebagian besar remaja kurang mengonsumsi serat sayur dan buah, dan sering mengkonsumsi makanan berpenyedap. Selain itu, remaja juga cenderung kurang melakukan aktifitas fisik. Mie merupakan makanan favorit anak-anak dan remaja bahkan orang dewasa sekalipun. Dengan permasalahan yang ada pengabdi berencana mengadakan pengabdian disalah satu desa binaan UMI yakni desa pucak, maros, lebih tepatnya di sekolah SMAN 13 Maros. Sekolah ini merupakan sekolah dengan jumlah siswa lumayan banyak tetapi rerata postur tubuh remajanya kecil, sehingga pengabdi merancang formula makanan yang digemari yang memiliki kandungan gizi yang tinggi, terutama kalsium. Metode pelaksanaan nantinya akan pengabdi berikan kuisioner diawal untuk mengukur kemampuan siswa, melakukan penyuluhan untuk menambah pemahaman siswa, dilanjutkan dengan mendemokan cara pembuatan mie dari daun kelor lalu melatih siswa(i) membuat mie secara mandiri, kemudian diakhir diberikan kuisioner sebagai bentuk evaluasi peserta. Hasil pengabdian ini sangatlah menarik minat dan antusias mereka terutama dikalangan guru-guru dan produk kami sangat digemari anak-anak sekolah. Kesimpulan kegiatan ini dimana siswa(i) mengalami peningkatan pemahaman dan produk mie sehat kelor kami disukai anak-anak serta guru-guru disekolah SMAN 13 Maros. Kata kunci : gizi; mie; kelor; SMAN 13Maros